Manufacturing of lower-limb custom fit prostethics sockets using reverse engineering - Curralo, Ana (2012)
The objective of this project is the onstruction of an orthopaedic prosthesis for a person who has been lower limb amputated, above the knee, taking attention to the specifications of the amputation stump. Through this method the actual process of prosthesis design in rehabilitation technology is improved by applying reverse engineering and additive manufacturing technologies. The outcome of this work is a personalized prosthesis building procedure that should allow a stump-socket best fit and avoid the numerous iterations done until a proper fit is obtained with traditional methods.